Transplantation of adipose‐derived mesenchymal stem cell sheets directly into the kidney suppresses the progression of renal injury in a diabetic nephropathy rat model. Issue 3 (6th November 2019) - Takemura, Shunsuke; Shimizu, Tatsuya; Oka, Masatoshi; Sekiya, Sachiko; Babazono, Tetsuya
Abstract: Aims/Introduction: Adipose‐derived mesenchymal stem cell (ASC) transplantation is a promising therapy for diabetic nephropathy (DN). However, intravascular administration of ASCs is associated with low engraftment in target organs. Therefore, we considered applying the cell sheet technology to ASCs. In this study, ASC sheets were directly transplanted into the kidneys of a DN rat model, and therapeutic consequences were analyzed. Materials and Methods: Adipose‐derived mesenchymal stem cells were isolated from adipose tissues of 7‐week‐old enhanced green fluorescent protein rats, and ASC sheets were prepared using a temperature‐responsive culture dish. A DN rat model was established from 5‐week‐old Spontaneously Diabetic Torii fatty rats. Seven‐week‐old DN rats ( n = 21) were assigned to one of the following groups: sham‐operated ( n = 6); ASC suspension (6.0 × 10 6 cells/mL) administered intravenously ( n = 7); six ASC sheets transplanted directly into the kidney ( n = 8). The therapeutic effect of the cell sheets was determined based on urinary biomarker expression and histological analyses. Results: The ASC sheets survived under the kidney capsule of the DN rat model for 14 days after transplantation. Furthermore, albuminuria and urinary tumor necrosis factor‐α levels were significantly lower in the ASC sheets transplanted directly into the kidney group than in the sham‐operated and ASC suspension administered intravenously groups ( P < 0.05). Histologically, the ASC sheets transplanted directly into the kidney group presented mild atrophy of the proximal tubule and maintained the renal tubular structure. Conclusions: Transplantation of ASC sheets directly into the kidney improved transplantation efficiency and suppressed renal injury progression. Therefore, the ASC sheet technology might be a promising novel treatment for DN. Abstract : Adipose‐derived mesenchymal stem cell sheet transplantation enhanced the engraftment efficiency and suppressed the progression of diabetic nephropathy.